Peran Mahasiswa KKN UINSU dalam Meningkatkan Kesadaran Kewirausahaan Syariah pada Masyarakat Desa Pahang Talawi Kabupaten Batu Bara - Abdurahman Abdurahman; Imsar Imsar; Dimas Pramudya; Muhammad Iqbal (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to analyze the role of UINSU’s Community Service Program (KKN) students in enhancing Islamic entrepreneurial awareness among the residents of Pahang Village, Talawi District, Batu Bara Regency. The KKN program serves as a platform for applying academic knowledge while empowering communities through educational, persuasive, and participatory approaches. The students introduced fundamental concepts of Islamic entrepreneurship, including principles of justice, honesty, sustainability, and the avoidance of riba, gharar, and maisir. Through a series of activities such as seminars, micro-business training sessions, financial management mentoring based on sharia principles, and simple business model simulations, the villagers began to show improved understanding of Islamic economic values. Moreover, the active involvement of students created an inclusive learning environment that was accessible to various community groups. The findings indicate that the presence of KKN students contributed positively to cultivating entrepreneurial motivation, particularly among youth and micro-business actors. This improvement was reflected in changes in mindset, interest in initiating halal businesses, and increased awareness of applying sharia principles in daily economic activities. Thus, the KKN program not only provides practical experience for students but also offers a tangible contribution to strengthening sharia-based economic empowerment at the village level.